2017
DOI: 10.15252/embj.201797278
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for antibacterial peptide self‐immunity by the bacterial ABC transporter McjD

Abstract: Certain pathogenic bacteria produce and release toxic peptides to ensure either nutrient availability or evasion from the immune system. These peptides are also toxic to the producing bacteria that utilize dedicated ABC transporters to provide self‐immunity. The ABC transporter McjD exports the antibacterial peptide MccJ25 in Escherichia coli. Our previously determined McjD structure provided some mechanistic insights into antibacterial peptide efflux. In this study, we have determined its structure in a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
115
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(131 citation statements)
references
References 56 publications
8
115
0
1
Order By: Relevance
“…In contrary, we have previously shown that the antibacterial peptide ABC transporter McjD, which confers bacterial cells with self‐immunity against the antibacterial peptide MccJ25, adopts distinct occluded conformations (Choudhury et al , 2014; Bountra et al , 2017) to other bacterial exporters including MsbA (Ward et al , 2007). The TMD is occluded to either side of the membrane in the presence or absence of nucleotides that was also supported by Pulsed Electron‐Electron Double Resonance (PELDOR) measurements in bicelles (Bountra et al , 2017). Occluded conformations have also been reported for other ABC transporters (Lin et al , 2015; Perez et al , 2015; Morgan et al , 2017).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In contrary, we have previously shown that the antibacterial peptide ABC transporter McjD, which confers bacterial cells with self‐immunity against the antibacterial peptide MccJ25, adopts distinct occluded conformations (Choudhury et al , 2014; Bountra et al , 2017) to other bacterial exporters including MsbA (Ward et al , 2007). The TMD is occluded to either side of the membrane in the presence or absence of nucleotides that was also supported by Pulsed Electron‐Electron Double Resonance (PELDOR) measurements in bicelles (Bountra et al , 2017). Occluded conformations have also been reported for other ABC transporters (Lin et al , 2015; Perez et al , 2015; Morgan et al , 2017).…”
Section: Introductionmentioning
confidence: 91%
“…All ABC transporters share a common architecture consisting of a transmembrane domain (TMD) for substrate recognition and transport, and a nucleotide‐binding domain (NBD) that converts the chemical energy of ATP into conformational changes for transport (Beis, 2015). The structures of several homodimeric (Dawson & Locher, 2006; Ward et al , 2007; Perez et al , 2015) and heterodimeric ABC transporters (Hohl et al , 2012; Noll et al , 2017) revealed distinct conformations and suggest, in combination with biophysical studies (e.g., EPR and NMR; Dong et al , 2005; Zou et al , 2009; Bountra et al , 2017; Timachi et al , 2017; Barth et al , 2018), that they undergo large conformational changes during transport. Their complex architecture is, however, a fundamental hurdle to fully understand the coupling between conformational changes, substrate binding, ATP binding and hydrolysis, and transport.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations